Dual roles of ULK1 (unc-51 like autophagy activating kinase 1) in cytoprotection against lipotoxicity. Issue 1 (2nd January 2020) - Park, Jeong Su; Lee, Da Hyun; Lee, Yu Seol; Oh, Eunji; Bae, Kwang-Hee; Oh, Kyoung-Jin; Kim, Hyunmi; Bae, Soo Han
ABSTRACT: Saturated fatty acid (SFA)-induced lipotoxicity is caused by the accumulation of reactive oxygen species (ROS), which is associated with damaged mitochondria. Moreover, lipotoxicity is crucial for the progression of nonalcoholic steatohepatitis (NASH). Autophagy is required for the clearance of protein aggregates or damaged mitochondria to maintain cellular metabolic homeostasis. The NFE2L2/NRF2 (nuclear factor, erythroid 2 like 2)-KEAP1 (kelch like ECH associated protein 1) pathway is essential for the elimination of ROS. ULK1 (unc-51 like autophagy activating kinase 1; yeast Atg1) is involved in the initiation of autophagy; however, its role in lipotoxicity-induced cell death in hepatocytes and mouse liver has not been elucidated. We now show that ULK1 potentiates the interaction between KEAP1 and the autophagy adaptor protein SQSTM1/p62, thereby mediating NFE2L2 activation in a manner requiring SQSTM1-dependent autophagic KEAP1 degradation. Furthermore, ULK1 is required for the autophagic removal of damaged mitochondria and to enhance binding between SQSTM1 and PINK1 (PTEN induced kinase 1). This study demonstrates the molecular mechanisms underlying the cytoprotective role of ULK1 against lipotoxicity. Thus, ULK1 could represent a potential therapeutic target for the treatment of NASH. Abbreviations : ACTB: actin beta; CM-H2 DCFDA:5-(and-6)-chloromethyl-2ʹ, 7ʹ-dichlorodihydrofluorescein diacetate; CQ: chloroquine; CUL3: cullin 3; DMSO: dimethyl sulfoxide; GSTA1: glutathione S-transferase A1; HA: hemagglutinin; Hepa1c1c7: mouse hepatoma cells; HMOX1/HO-1: heme oxygenase 1; KEAP1: kelch like ECH associated protein 1; LPS: lipopolysaccharides; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MAPK8/JNK: mitogen-activated protein kinase 8; MEF: mouse embryonic fibroblast; MFN1: mitofusin 1; MTT: 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide; NASH: nonalcoholic steatohepatitis; NFE2L2/NRF2: nuclear factor, erythroid 2 like 2; NQO1: NAD(P)H quinone dehydrogenase 1; PA: palmitic acid; PARP: poly (ADP-ribose) polymerase 1; PINK1: PTEN induced kinase 1; PRKAA1/2: protein kinase AMP-activated catalytic subunits alpha1/2; PRKN/PARK2: parkin RBR E3 ubiquitin protein ligase; PRKC/PKC: protein kinase C; RBX1: ring-box 1; ROS: reactive oxygen species; SFA: saturated fatty acid; siRNA: small interfering RNA; SQSTM1/p62: sequestosome 1; TOMM20: translocase of outer mitochondrial membrane 20; TUBA: tubulin alpha; TUNEL: terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling; ULK1: unc-51 like autophagy activating kinase 1